Treatment Guidelines for Rheumatologic Manifestations of Sjögren's Syndrome: Use of Biologic Agents, Management of Fatigue, and Inflammatory Musculoskeletal Pain. Issue 4 (3rd March 2017) - Carsons, Steven E.; Vivino, Frederick B.; Parke, Ann; Carteron, Nancy; Sankar, Vidya; Brasington, Richard; Brennan, Michael T.; Ehlers, William; Fox, Robert; Scofield, Hal; Hammitt, Katherine M.; Birnbaum, Julius; et al.
Abstract : Objective: The Sjögren's Syndrome Foundation clinical practice guidelines (CPGs) are designed to improve quality and consistency of care in Sjögren's syndrome by offering recommendations for management. Methods: Management questions for the systemic manifestations of Sjögren's syndrome were posed by the CPG committee with input from patients and rheumatologists. Clinical questions were assigned to a topic review group that performed systematic reviews and data extraction and drafted guidelines. Quality of evidence and strength of recommendation were rated using the American Society of Clinical Oncology's modification of the Grading of Recommendations Assessment, Development, and Evaluation. Guideline recommendations were reviewed by a consensus expert panel (CEP) composed of 30–40 clinicians from academia and community practices, as well as registered nurses and patients, using a modified Delphi process. A CEP agreement level of 75% was set as a minimum for adoption of a guideline recommendation. Results: Consensus was achieved for 19 recommendations; for 11 additional modules, available data were insufficient to allow a recommendation to be formulated. Of the 19 recommendations, 15 required 1 Delphi round, 2 required 2 rounds, and 2 required 3 rounds. Conclusion: Key recommendations include a decision tree for the use of oral disease‐modifying antirheumatic drugs for inflammatory musculoskeletal pain, use of self‐care measures and advice regarding exercise to reduce fatigue, and the use of rituximab in selected clinical settings for oral and ocular dryness and for certain extraglandular manifestations, including vasculitis, severe parotid swelling, inflammatory arthritis, pulmonary disease, and mononeuritis multiplex. The CPG committee strongly discouraged the use of tumor necrosis factor inhibitors for sicca symptoms and for the majority of clinical contexts in primary Sjögren's syndrome.